Statin Therapy for Hyperlipidemic Patients With Chronic Kidney Disease and End-Stage Renal Disease: A Retrospective Cohort Study Based on 925,418 Adults in Taiwan - Sung, Fung-Chang; Jong, Ying-Chin; Muo, Chih-Hsin; Hsu, Chih-Cheng; Tsai, Wen-Chen; Hsu, Yueh-Han (Frontiers in Pharmacology, 2022)
Background: For non-dialysis patients with hyperlipidemia, statins may provide clinical benefits in reducing mortality risk; however, the optimal treatment for dialysis patients with hyperlipidemia remains debatable. We evaluated mortality risks for hyperlipidemic patients with renal disorders associated with statin therapy, using insurance claims data of Taiwan. Methods: From hyperlipidemic patients diagnosed in 2000-2011, we identified 555,153 patients receiving statins treatment for at least 90 days continuously and 1,141,901 non-statin users, then randomly selected, from both groups, propensity score matched subcohorts of statin users and non-users in 1:1 pair by renal function: 415,453 pairs with normal renal function (NRF), 43,632 pairs with chronic kidney disease (CKD) and 3,624 pairs with end-stage renal disease (ESRD). We compared mortalities, by the end of 2016, from all-causes, cancer, heart disease and septicemia between statin users and non-users and between hydrophilic-statin users and lipophilic-statin users. The Cox method estimated ST users to non-user hazard ratios. Time-dependent model was also conducted as sensitivity analysis. Results: Mean ages were 58.7 ± 10.7, 64.2 ± 10.7 and 62.2 ± 10.8 years in NRF, CKD and ESRD groups, respectively. Compared with non-users, statin users had reduced mortality risks from all-causes for 32 to 38%, from cancer for 37 to 46%, from heart disease for 6 to 24% and from septicemia for 17 to 21% in all 3 renal groups. The hydrophilic-statin therapy was superior than the lipophilic-statin therapy, particularly for reducing deaths from all-causes and cancer. The results under time-dependent model were similar. Conclusion: Statin therapy is associated with reduced all-causes and non-cardiovascular mortality in ESRD patients.